The relationship between job satisfaction and pay satisfaction with organisational commitment among academics in Higher Learning Institutions in Klang Valley - Ramakrishnan, Revati (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2014)
In the last few years, there has been an increase in research conducted which relates to organizational commitment among the various industrial groups. Given the established importance of higher learning institutions (HLIs), it is not arguable/it cannot be denied that academics are one of the most important factors for an HLI to excel and flourish. It is observed that from the extensive research that is conducted, there are limited studies done using academic samples and this is especially so in the Klang Valley. This study is designed to explore the relationship between job satisfaction and pay satisfaction as it relates to organizational commitment among academics of HLIs in Klang Valley. Specifically, this study seeks to study the following: (1) the relationship between job satisfaction and organizational commitment; (2) the relationship between pay satisfaction and organizational commitment; and (3) the difference in pay satisfaction between academics of public and private HLIs. Questionnaires were distributed to 300 participants who were recruited from public and private HLIs. Statistical analyses specifically regression, correlation and independent t-test is used to analyze the findings in the relationship of job satisfaction and pay satisfaction with organizational commitment. The findings show that there is a significant relationship between job satisfaction and organizational commitment (r = 0.605) and between pay satisfaction and organizational commitment (r = 0.630). Results also indicated that the academics from the public institutions have higher pay satisfaction than the academics from private institutions. The results of the study have valuable implications for all involved in the leadership and management of Higher Education Division, college administration and educators themselves because educational organizations, like all other organizations, require constant monitoring to identify areas for possible change and development especially when workplace practices have been increasingly changing since the last few decades. Findings of this study would also be useful to Human Resource managers in determining an employees's worth by the market value of their labour.